11-year solar cycle influences on the late-wintertime South Asian jet variability - Ma, Hedi; Wang, Ruili; Li, Xing; Lai, Anwei; Li, Xiao (Frontiers in Earth Science, 2023)
The South Asian jet leading wave train (SAJLWT) is a zonally elongated and equivalently barotropic stationary Rossby wave train along the wintertime South Asian subtropical jet, which stands out as the leading empirical orthogonal function mode of monthly meridional winds at the upper troposphere over southern Eurasia. The SAJLWT is closely related to weather and climate extremes over southern Eurasia, but up to now, the mechanisms of SAJLWT variability are still not fully understood. The present study reveals a significant 11-year solar cycle (SC) influence on the SAJLWT variability in late winter (January–March). The in-phase correlation between the SC and the SAJLWT is not only statistically significant but also consistent over time. Associated with the solar-induced SAJLWT anomalies, significant surface cooling exists over northeastern Africa and Middle East, while significant positive precipitation anomalies appear over southern China. Two routes of mechanisms are presented to clarify the SC–SAJLWT linkage. One is due to the solar-induced northwest–southeast tilted North Atlantic Oscillation (TNAO) pattern, which may reflect a “top–down” solar forcing and the ocean–atmosphere couplings in the North Atlantic Ocean. This TNAO pattern would trigger southeastward wave activity fluxes toward the SAJ, thus significantly impacting the upstream portions of the SAJLWT pattern. The other mechanism involves weakened convection over the Maritime Continent (MC) region, reflecting solar-induced weakening of Pacific Walker Circulation via “bottom–up” processes. The MC convection anomaly would also excite a SAJLWT-like circulation pattern. Our analysis highlights that the solar “top–down” and “bottom–up” mechanisms may act in concert to exert a significant impact on the SAJLWT and indicates that the SC forcing is an appreciable source of decadal predictability in southern Eurasia.